2024
DOI: 10.1136/jitc-2023-007895
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid epithelial-mesenchymal status of lung cancer dictates metastatic success through differential interaction with NK cells

Monica Parodi,
Giovanni Centonze,
Fabio Murianni
et al.

Abstract: BackgroundEpithelial to mesenchymal transition (EMT) endows cancer cells with pro-metastatic properties, which appear most effective when cells enter an intermediate hybrid (H) state, characterized by integrated mesenchymal (M) and epithelial (E) traits. The reasons for this advantage are poorly known and, especially, it is totally unexplored whether the interplay between H-cells and NK cells could have a role. Here we characterize the pro-metastatic mechanics of non-small cell lung cancer (NSCLC) H-cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
(39 reference statements)
0
1
0
Order By: Relevance
“… 93 In particular, lung cancer cells undergoing an intermediate EMT state have been recently shown to avoid NK cell attacks by both reducing chemokine production and inhibiting NK cell cytotoxic response. 146 In the case of pancreatic adenocarcinoma (PA), it has been demonstrated that PA cell lines deriving from primary or metastatic tumors display a different susceptibility to NK cells, with metastatic ones displaying EMT-related gene expression and phenotype and an increased resistance to NK cell-mediated lysis. 147 …”
Section: Tumor-nk Cell Interactionsmentioning
confidence: 99%
“… 93 In particular, lung cancer cells undergoing an intermediate EMT state have been recently shown to avoid NK cell attacks by both reducing chemokine production and inhibiting NK cell cytotoxic response. 146 In the case of pancreatic adenocarcinoma (PA), it has been demonstrated that PA cell lines deriving from primary or metastatic tumors display a different susceptibility to NK cells, with metastatic ones displaying EMT-related gene expression and phenotype and an increased resistance to NK cell-mediated lysis. 147 …”
Section: Tumor-nk Cell Interactionsmentioning
confidence: 99%